Audit Sistem Informasi Aplikasi Absensi Greatday Menggunakan Framework Cobit 5 - Ristia Sekar Ayu Nur Afifah; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
An information system audit is carried out to ensure that system procedures in the company are running well, using the Cobit 5 framework in auditing the attendance system because there is a system that has not been audited before and there are deficiencies where there are no warning notifications for employees doing work absences, the accuracy of the location of attendance often changes -change with the location of employee attendance, and must check 2 applications to view employee attendance log archives. The results obtained are the order of the domain with the highest score, namely the MEA01 domain, the maturity level value is 23.84, the Fully Achieved achievement value, gets the Optimized Level in IT capabilities, and the gap value is 19.84 from the target level 4. DSS01, the maturity level value is 17.59, the Fully Achieved achievement value , got the Optimized Level level in IT capabilities, and a gap value of 13.59. The order of the highest scoring domain is the MEA01 domain with a maturity level value of 23.84 with a gap value of 19.84, DSS01 with a maturity level value of 17.59 with a gap value of 13.59. The results of the gap analysis obtained show that the current conditions still achieve better results, application absences are used quite satisfactorily in the features that have been provided, are not sure about the technicalities which still need to be reviewed and improved so that they are even better, it can be said that the current Greatday application used is sufficient maximum in providing attendance features that run